1998
DOI: 10.1007/bf01451013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of tetranectin levels in serum and synovial fluid of patients with rheumatoid arthritis, seronegative spondylarthritis and osteoarthritis

Abstract: Tetranectin (TN) was assessed in paired synovial fluid (SF) and serum (S) samples from 27 patients with rheumatoid arthritis (RA), 23 with seronegative spondylarthritis (SSA) and 22 with osteoarthritis (OA). RA patients had a stronger correlation between serum and SF TN and a higher SF/S TN ratio than did SSA and OA patients. Moreover, the SF/S TN ratio exceeded 1 in most RA patients but not in SSA and OA patients, indicating the possibility of intra-articular TN synthesis in RA. A strong correlation of serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
0
15
1
Order By: Relevance
“…Tetranectin is a phosphorylated glycoprotein that has been hypothesized to regulate mineral deposition within the bone (50,51); however, the role of tetranectin in the pathogenesis of OA is currently unclear. Tetranectin has been implicated in the impaired regulation of fibrinolysis and is associated with the inflammatory process in RA (52,53). However, the present study demonstrated that tetranectin expression was decreased in the ICRS3 group compared with the ICRS1 group.…”
Section: Discussioncontrasting
confidence: 68%
“…Tetranectin is a phosphorylated glycoprotein that has been hypothesized to regulate mineral deposition within the bone (50,51); however, the role of tetranectin in the pathogenesis of OA is currently unclear. Tetranectin has been implicated in the impaired regulation of fibrinolysis and is associated with the inflammatory process in RA (52,53). However, the present study demonstrated that tetranectin expression was decreased in the ICRS3 group compared with the ICRS1 group.…”
Section: Discussioncontrasting
confidence: 68%
“…130 Although the role of tetranectin in the pathogenesis of osteoarthritis is currently unknown, it has been implicated in the impaired regulation of fibrinolysis associated with the inflammatory process in rheumatoid arthritis. 131 α1-Antichymotrypsin is a serine proteinase inhibitor that helps regulate diverse physiologic processes such as coagulation, fibrinolysis, complement activation, angiogenesis, apoptosis, inflammation, and neoplasia and viral pathogenesis 132 and thus potentially can prevent the degradation of connective tissue components. The α-induced protein of TNF is also referred to as TNF-secreted glycoprotein 6 and functions to modulate the interaction between hyaluronan and cell-surface receptor CD44.…”
Section: Growth Factorsmentioning
confidence: 99%
“…Its overexpression in serum and synovial fluid of RA as compared to osteoarthritis and SpA have been reported earlier [65]. Vitamin D binding protein (GC), a glycoprotein, was found to be >1.5-fold upregulated in RA and has been reported earlier in synovial fluid and serum samples of RA [66,67].…”
Section: Resultsmentioning
confidence: 86%